Near Eastern Plant Domestication: A History of Thought. (June 2017) - Abbo, Shahal; Gopher, Avi
Abstract : The Agricultural Revolution and plant domestication in the Near East (among its components) have fascinated generations of scholars. Here, we narrate the history of ideas underlying plant domestication research since the late 19th century. Biological and cultural perspectives are presented through two prevailing models: one views plant domestication as a protracted, unconscious evolutionary mutualistic (noncentric) process. The second advocates a punctuated, knowledge-based human initiative (centric). We scrutinize the research landscape while assessing the underlying evolutionary and cultural mechanisms. A parsimony measure indicates that the punctuated-centric view better accords with archaeological records, and the geobotany and biology of the species, and requires fewer assumptions. The protracted alternative requires many assumptions, does not account for legume biology, fails to distinguish domestication from postdomestication changes, and, therefore, is less parsimonious. Trends: Ever since Darwin, plant domestication has been conceptualized as an evolutionary continuum in various frameworks. Genome-wide sequence polymorphism data are being used in plant domestication studies to: analyze domestication selection signatures; estimate the number of plant domestication and crop evolution selective sweeps; assess the number of domestication events and putative locations; and evaluate the relative role of reproductive isolation from wild progenitors versus introgressive hybridization with wild relatives during crop evolution. In attempts to corroborate theoretical scenarios, archaeologists tend to incorporate ethnographic data in their plant domestication models. The current incorporation of biological and cultural niche-construction theoretical considerations in plant domestication models is being used mostly to redress previous coevolutionary domestication models that rely on unconscious prey–predator relations, thereby minimizing the role of human consciousness and agency.